Connections among geographical and historical descriptions in Aeneid 8 (Circe de clásicos y modernos, 2018)
Aeneid ́s Book 8 offers a large ver-sion of Roman History from the beginnings of Janus and Saturnus to Accius ́ battle. Historic account is developed in two episodes: Evander and Aeneas ́ tour through Palanteum and the description of Vulcanus ́ shield. Both episodes can be taken as ekphrasis and the hypothesis of this paper considers that both must be read in a complementary way in order to assume that Virgilian proposal about history, unlike Livius ́, consists of a series of foundations written on the memory of Roman natural and urban geography.
Keywords: Aeneid; Aeneas’ shield; ekphrasis; urban geography; roman History